ЕВОЛУЦИЈА ГАСТРОНОМСКОГ МЕНАЏМЕНТА: СИСТЕМАТСКИ ПРЕГЛЕД ЛИТЕРАТУРЕ И НОВЕ ПЕРСПЕКТИВЕ У ПОСТПАНДЕМИЈСКОМ ДОБУ - Popović, Anđelka; Conić, Momčilo; Vukolić, Dragan (Turističko poslovanje, 2025)
The aim of this paper is to systematically examine the evolution of gastronomic management as both a scientific and practical discipline, with a particular emphasis on the post-COVID-19 era. A systematic literature review was conducted for the period 2010–2024, including 57 peer-reviewed academic publications retrieved from relevant scholarly databases. The analysis resulted in the identification of five dominant thematic clusters: theoretical foundations, practical management strategies, digitalisation and innovation, crisis management in the context of COVID-19, and sustainability. Through the application of thematic mapping and visual tools (PRISMA diagram, timeline chart), the paper illustrates shifts in research focus, identifies methodological gaps, and proposes directions for further inquiry. The findings suggest that gastronomic management is evolving into an interdisciplinary, innovation-driven, and sustainability-oriented field, integrating strategic planning, digital technologies, and social responsibility within the framework of the post-pandemic hospitality environment.
Keywords: gastronomski menadžment; sistemski pregled; digitalizacija; održivost; COVID-19; tematska mapa